The Impact of YAG Laser Capsulotomy on Intraocular Pressure - Dr. MAISOON MOHAMED; Dr. Rania Abdullah Ali Alkhoja; Dr. Algharib Albaghdadi Alshraa; Dr. Amal Nouri . Elthabet (Aljameai, 2025)
Abstract: Background: Neodymium-doped yttrium aluminum garnet (Nd:YAG) laser capsulotomy is the gold standard for treating posterior capsule opacification (PCO). While effective, it is associated with complications, most commonly a rise in intraocular pressure (IOP). This study investigates the relationship between procedural parameters (capsulotomy size and total laser energy) and the incidence of complications.Methods: A longitudinal study was conducted to follow up forty-eight pseudophakic patients with visually significant PCO underwent Nd:YAG laser capsulotomy at Tripoli Eye Hospital. Patients were monitored for IOP changes, cystoid macular edema (CME), and other complications at 1-hour, 1-week, and 1-month post-procedure. Statistical analysis assessed correlations between laser parameters and outcomes.Results: A significant IOP spike was observed in treated eyes compared to untreated fellow eyes at 1-hour post-procedure (p < 0.05). This elevation was more pronounced and persistent in eyes with larger capsulotomy sizes (>3.9 mm) and higher total laser energy (>40 shots). Transient macular thickening was noted but resolved by one month, with no significant correlation to laser parameters. No cases of retinal detachment or severe inflammation occurred. Pre-existing glaucoma was a risk factor for sustained IOP elevation.Conclusion: Nd:YAG laser capsulotomy is a safe and effective procedure. However, IOP elevation is a common complication, strongly correlated with larger capsulotomy size and higher total energy. Using the minimal effective energy and a conservative capsulotomy size, particularly in glaucoma patients, is recommended to minimize complications.المستخلص:الخلفية: يُعد استئصال المحفظة باستخدام ليزر YAG المشوب بالنيوديميوم (Nd:YAG) المعيار الذهبي لعلاج تعتيم المحفظة الخلفية (PCO). وعلى الرغم من فعاليته، إلا أنه يرتبط بمضاعفات، وأكثرها شيوعًا ارتفاع ضغط العين (IOP). تبحث هذه الدراسة في العلاقة بين المعايير الإجرائية (حجم استئصال المحفظة وإجمالي طاقة الليزر) ومعدل حدوث المضاعفاتالطريقة: أُجريت دراسة طولية لمتابعة ثمانية وأربعين مريضًا مصابين بضمور عدسة كاذب مع PCO ذو دلالة بصرية، خضعوا لاستئصال المحفظة بالليزر Nd:YAG في مستشفى طرابلس للعيون. تمت مراقبة المرضى بحثًا عن تغيرات ضغط العين، والوذمة البقعية الكيسية (CME)، ومضاعفات أخرى بعد ساعة واحدة، وأسبوع واحد، وشهر واحد من العملية. قيّم التحليل الإحصائي الارتباطات بين معايير الليزر والنتائج.النتائج: لوحظ ارتفاع كبير في ضغط العين في العيون المعالجة مقارنةً بالعيون غير المعالجة بعد ساعة واحدة من العملية (p <0.05). كان هذا الارتفاع أكثر وضوحًا واستمرارًا في العيون ذات أحجام استئصال المحفظة الأكبر (>3.9 مم) وطاقة الليزر الكلية الأعلى (>40 طلقة). لوحظ سماكة بقعية عابرة ولكنها اختفت بعد شهر واحد، دون وجود ارتباط كبير بمعايير الليزر. لم تحدث أي حالات انفصال شبكي أو التهاب شديد. كان الجلوكوما الموجود مسبقًا عامل خطر لارتفاع ضغط العين المستمرالخلاصة: يُعد استئصال المحفظة باستخدام ليزر Nd:YAG إجراءً آمنًا وفعالًا. ومع ذلك، يُعد ارتفاع ضغط العين من المضاعفات الشائعة، ويرتبط ارتباطًا وثيقًا بحجم المحفظة الأكبر والطاقة الكلية الأعلى. يُنصح باستخدام الحد الأدنى من الطاقة الفعالة وحجم المحفظة المحافظ، خاصةً لدى مرضى الجلوكوما، لتقليل المضاعفات